Anodic Dissolution of API X70 Pipeline Steel in Arabian Gulf Seawater after Different Exposure Intervals - El-Sayed M. Sherif; Abdulhakim A. Almajid (Journal of Chemistry)
The anodic dissolution of API X70 pipeline steel in Arabian Gulf seawater (AGSW) was investigated using open-circuit potential (OCP), electrochemical impedance spectroscopy (EIS), cyclic potentiodynamic polarization (CPP), and current-time measurements. The electrochemical experiments revealed that the X70 pipeline steel suffers both general and pitting corrosion in the AGSW solution. It was found that the general corrosion decreases as a result of decreasing the corrosion current density (jcorr), corrosion rate (Rcorr) and absolute currents as well as the increase of polarization resistance of X70 with increasing the exposure time. On the other hand, the pitting corrosion was found to increase with increasing the immersion time. This was confirmed by the increase of current with time and by the SEM images that were obtained on the steel surface after 20 h immersion before applying an amount of 0–.35 V versus Ag/AgCl for 1 h.